The Effects of Disc Flexibility on the Sealing Performance of Spring-loaded Main Steam Pressure Relief Valves. (2015) - Chen, H.; Yu, X.H.; Tan, J.P.
Abstract: In this paper, three-dimensional finite element methods were carried out to investigate the disc flexibility effects on the PRV sealing performances. For the PRV subjected to inner pressure, the calculation results show that the location of maximum contact press on the sealing ring varies from the outer region to the inner region when the inner pressure increases from 1 to 7 MPa. The PRV with a more flexible disc exhibits a higher maximum contact press, thus resulting in a better sealing performance. For the PRV subjected to impact load in the case of re-closing process, the effects of disc flexibility on the PRV sealing performance was also studied. The finite calculation results indicate that the maximum plastic deformation is located in the outer region of the disc sealing ring and the sliding was occurred on the sealing ring, which is validated by experiments. The maximum plastic deformation and the displacement of sliding increase with a rise of disc flexibility. The plastic deformation and sliding has little effect on the sealing performance when the inner pressure close to setting pressure. As a result, the PRV with a higher disc flexibility showed a better sealing performance after re-closing impact process. The calculation results confirmed that reasonable disc flexibility is very important to guarantee a good sealing performance of PRV.